Images of a complex world the art and poetry of chaos - Chapman, Robin S. (World Scientific Pub. Co., 2005)
With the poems written by winner of the Posner Poetry Award from the Council of Wisconsin Writers in 2005, this coffee-table book will delight and inform general readers curious about ideas of chaos, fractals, and nonlinear complex systems. Developed out of ten years of interdisciplinary seminars in chaos and complex systems at the University of Wisconsin-Madison, it features multiple ways of knowing : Robin Chapman's poems of everyday experience of change in a complex world, associated metaphorically with Julien Clinton Sprott's full-color computer art generated from billions of versions of only three simple equations for strange attractors, Julia sets, and iterated function systems; his definitions of 39 key terms; a mathematical appendix; and even a multiple-choice quiz to test understanding. Accompanied by a CD-ROM of the poet reading 13 poems and 1,000 images of chaos art from which slide shows can be generated and 100 high-resolution posters created, the book has a foreword by Cliff Pickover, author of A Passion for Mathematics